Evaluating the Effectiveness of Mutation Operators on the Behavior of Genetic Algorithms Applied to Non-deterministic Polynomial Problems - Hasan, B.H.F.; Saleh, M.S.M. (Informatica)
Evaluating the Effectiveness of Mutation Operators on the Behavior of Genetic Algorithms Applied to Non-deterministic Polynomial Problems